1991
DOI: 10.1002/em.2850180204
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bleomycin‐induced mutagenic functions related to the PSO4 (= XS9) gene of saccharomyces cerevisiae

Abstract: In the present work we analyse some properties of the pso4-1 (= xs9) mutant of the yeast Saccharomyces cerevisiae, which is blocked in both reverse mutation and recombination. We have applied the "apparent survival test" as a method to characterize putative inducible error-prone repair activities related to the PSO4 gene. As the mutagenic agent we have used bleomycin, which is an antitumour radiomimetic antibiotic. Survival, reverse mutation yield, and reverse mutation frequency were determined as a function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…This biphasic response could be due to the induction of repair enzymes. Interestingly, in our laboratory it has been recently shown that the resistant component of these curves depends at least in part on BLM-inducible repair (39). Moreover, the RAD6 gene is induced by DNA damage during the log phase of growth (21).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This biphasic response could be due to the induction of repair enzymes. Interestingly, in our laboratory it has been recently shown that the resistant component of these curves depends at least in part on BLM-inducible repair (39). Moreover, the RAD6 gene is induced by DNA damage during the log phase of growth (21).…”
Section: Discussionmentioning
confidence: 98%
“…In different lines of eukaryotic cells, BLM produces inhibition of DNA synthesis (10) as well as cell cycle G2 delay (19,38). With phages, bacteria, and yeast cells, it was demonstrated that this drug is recombinogenic and mutagenic (11,23,39,42). Analysis of BLM-induced mutagenesis in repackaged lambda phage suggests SOS repair dependence (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, the number of revertants lys → LYS were scored ( 12 , 13 ). Mutation frequency M(x,y) and mutation yield Y(x,y) were calculated as: M(x,y) = Nm / Ns; Y(x,y) = Nm / No, where Nm is the number of mutants per mL, No is the number of treated cells per mL, x the absorbed dose, and y the dose of modulators ( 16 , 19 , 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…No: número de células tratadas por mL, Nm: número de mutantes por mL, x: dosis absorbida de rayos gamma, y: dosis de los productos naturales (31,35,36) .…”
Section: Tratamientos Tratamientos Simples Y Combinadosunclassified